Penerapan Digital Government Melalui Website Taring Dukcapil di Dinas Kependudukan dan Pencatatan Sipil Kota Denpasar - Ketut Ryan Adi Nugraha; Komang Adi Sastra Wijaya; Kadek Wiwin Dwi Wismayanti (Ethics and Law Journal: Business and Notary, 2023)
The Online Registration Website for Population and Civil Registration Administration (Taring Dukcapil) is service innovation introduced by the Population and Civil Registration Office of Denpasar City. This website was established as an effort to provide online civil administration service during the large-scale social restrictions and continued to be used post-pandemic. The method used in this research is qualitative with descriptive approach. The data for this research was gathered through observations, interviews, and documentations. This research utilized the dimensions of digital government proposed by Lee, which consist of data, technology, service, people, and governance. The result of this research shows that the implementation of the Taring Dukcapil website as a platform for delivering online civil administration services has been working. However, there are still some aspects that are not optimal. Therefore, measures are required to enhance these five dimensions so that the implementation of digital government through the website can run more optimally.